2012
DOI: 10.1002/crat.201200131
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and tribological properties of Mo‐doped WSe2 Nanolamellars

Abstract: The Mo‐doped WSe2 nanolamellars have been successfully prepared via solid‐state thermal (750 °C) reaction between micro‐sized W, Mo with Se powders under inert atmosphere in a closed reactor and characterized by X‐ray diffractometer (XRD), scanning electron microscopy (SEM) and transmission electron microscopy (TEM). It was found that the morphologies of the as‐prepared products changed from microplates to nanolamellars to aggregations composed of nanoparticles with the doping of Mo powders. And the sizes of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Over the past decades, a number of experimental and theoretical studies have been dedicated to modify LTMDs' properties through the doping method mainly due to the attractive results brought by the dopants. Wenjing Li et al 18 found that the friction coefficient of the base oil containing Mo-doped WSe 2 nanolamellars was lower and more stable than that of pure WSe 2 nanolamellars partly because the Mo-WSe 2 nanoakes with thinner and smaller morphologies could form a more stable tribolm on the rubbing surface. Similarly, Xiaopeng Qin et al 19 have nished a research on the microstructure, mechanical and tribological of Ti-doped MoS 2 composite coatings, which manifests the hardness and adhesion of the composite coatings reached its maximum within a certain range of Ti content and doped Ti improved the tribological properties of pure MoS 2 as well.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decades, a number of experimental and theoretical studies have been dedicated to modify LTMDs' properties through the doping method mainly due to the attractive results brought by the dopants. Wenjing Li et al 18 found that the friction coefficient of the base oil containing Mo-doped WSe 2 nanolamellars was lower and more stable than that of pure WSe 2 nanolamellars partly because the Mo-WSe 2 nanoakes with thinner and smaller morphologies could form a more stable tribolm on the rubbing surface. Similarly, Xiaopeng Qin et al 19 have nished a research on the microstructure, mechanical and tribological of Ti-doped MoS 2 composite coatings, which manifests the hardness and adhesion of the composite coatings reached its maximum within a certain range of Ti content and doped Ti improved the tribological properties of pure MoS 2 as well.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, NbSe 2 were successfully synthesized by a facile thermal solid-state reaction [14]; then, the as-prepared NbSe 2 was coated with Ni layers by electroless plating [15]. Details of the electroless plating are as follows: NbSe 2 powder was firstly coarsened by ultrasonic treatment in a concentrated H 2 SO 4 solution for 20 min.…”
Section: Methodsmentioning
confidence: 99%
“…The Ti-doped NbSe 2 nanoplatelets were successfully fabricated by ball milling micro-sized Nb, Ti and Se powders at a molar ratio of 0.91:0.09:2.2 for 10 h first (Li et al , 2012; Zhang et al , 2014). Then, the mixed powders were put into the quartz tubes, exhaust air then seal.…”
Section: Methodsmentioning
confidence: 99%